Hamlet - Shakespeare, William; Bloom ,Harold; Thiel, Joan E.; Myers, Emerson; Shakespeare, William, 1564-1616.; Hartke Theatre (Organization : Catholic University of America); Richard L. Coe Theater Programs Collection (Library of Congress) (Viva , New Delhi, 2008)
The Catholic University of America, the Gilbert V. Hartke Theatre presents "Hamlet," by William Shakespeare, directed by James D. Waring, settings and lighting by Mr. Waring, costumes by Joan E. Thiel, electronic sounds by Emerson Meyers, production stage manager Mary E. Holden.
Includes index.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English drama; Theater programs -- Washington (D.C.); Theater programs -- 1971.